Polysaccharide diversity in VNI isolates of Cryptococcus neoformans from Roraima, Northern Brazil. Issue 10 (October 2019) - Dal Pupo, Halan D.; Sena, Bianca A.G.; Reis, Flavia C.G.; Machado, Lumena; Fortes, Silvana T.; de Almeida Junior, João N.; Godinho, Rodrigo M.C.; Rodrigues, Marcio L.
Abstract: Species of the Cryptococcus genus comprise environmental, encapsulated fungal pathogens that cause lethal meningitis in immunosuppressed individuals. In humans, fungal uptake of hypocapsular Cryptococcus by macrophages was associated with high fungal burden in the cerebrospinal fluid and long-term patient survival. On the basis of the key role of the cryptococcal capsule in disease, we analyzed the diversity of capsular structures in 23 isolates from pigeon excreta collected in the cities of Boa Vista, Bonfim and Pacaraima, in the state of Roraima (Northern Brazil). All isolates were identified as Cryptococcus neoformans (VNI genotype) by MALDI-TOF mass spectrometry. Through a combination of fluorescence microscopy, flow cytometry, ELISA and spectrophotometric methods, each isolate was characterized at the phenotypical level, which included measurements of growth rates at 30 and 37 °C, pigmentation, cell body size, capsular dimensions, serological reactivity, urease production and ability to produce extracellular glucuronoxylomannan (GXM), the main capsular component of C. neoformans . With the exception of melanization, a formidable diversity was observed considering all parameters tested in our study. Of note, hyper and hypo producers of GXM were identified, in addition to isolates with hyper and hypo profiles of reactivity with a polysaccharide-binding monoclonal antibody. Capsular dimensions were also highly variable in the collection of isolates. Extracellular GXM production correlated positively with capsular dimensions, urease activity and cell size. Unexpectedly, GXM concentrations did not correlate with serological reactivity with the cryptococcal capsule. These results reveal a high diversity in the ability of environmental C. neoformans to produce capsular components, which might impact the outcome of human cryptococcosis.